2009
DOI: 10.1111/j.1467-8276.2008.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Spatial Arbitrage with Transport Capacity Constraints and Endogenous Transport Prices

Abstract: This article solves a high-frequency model of price arbitrage incorporating storage and trade when the amount of trade is limited by transport capacity constraints. In equilibrium there is considerable variation in transport prices because transport prices rise when the demand to ship goods exceeds the capacity limit. This variation is necessary to attract shipping capacity into the industry. In turn, prices in different locations differ by a time varying amount. Thus while the law of one price holds, it holds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…As noted below we have not been able to substantiate a conjecture implied by Coleman (2009) that a fall in the frequency of stock-outs might contribute to the smaller violations of the law of one price. For example, when prices rise above equilibrium sellers might mistake that for a permanent rise and increase their imports.…”
Section: A Model Of Excess Demand and Supplycontrasting
confidence: 74%
See 1 more Smart Citation
“…As noted below we have not been able to substantiate a conjecture implied by Coleman (2009) that a fall in the frequency of stock-outs might contribute to the smaller violations of the law of one price. For example, when prices rise above equilibrium sellers might mistake that for a permanent rise and increase their imports.…”
Section: A Model Of Excess Demand and Supplycontrasting
confidence: 74%
“…In a recent article, Coleman (2009) has shown that constraints in storage can cause violations of the law of one price. For example, an adverse output shock in a market might bring inventory levels down to zero, and prices will then depart from the law of one price until new shipments arrive.…”
Section: What Caused the Improvement In Market Efficiency?mentioning
confidence: 99%
“…Technologies, which are the source of SO2 emissions, normally decrease as the GDP per capita increases. Therefore, where most countries remain in the developing stage, the SO2 emissions per capita are increasing at lower economic levels and begins to decrease at higher GDP levels, which is consistent with recent studies (e.g., Iwami 2004;Yaguchi et al 2007;Coleman 2009). SO2 is considered a local pollutants that is easier to control than global emissions.…”
Section: Co2supporting
confidence: 78%
“…However, this conclusion holds only if trade is instantaneous. If trade takes time as in Coleman (2009), it can be rational to store imported commodities.…”
Section: The Competitive Storage Modelmentioning
confidence: 99%